2011
DOI: 10.1371/journal.pone.0021390
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Regulatory Characteristics of the Mycobacterial Dephosphocoenzyme A Kinase: Implications for the Universal CoA Biosynthesis Pathway

Abstract: Being vastly different from the human counterpart, we suggest that the last enzyme of the Mycobacterium tuberculosis Coenzyme A biosynthetic pathway, dephosphocoenzyme A kinase (CoaE) could be a good anti-tubercular target. Here we describe detailed investigations into the regulatory features of the enzyme, affected via two mechanisms. Enzymatic activity is regulated by CTP which strongly binds the enzyme at a site overlapping that of the leading substrate, dephosphocoenzyme A (DCoA), thereby obscuring the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…3537 These studies, together with the availability of crystal structures of a number of CoA pathway enzymes for use in structure-guided drug design, provided further support for investigating the CoA pathway as an attractive source of new TB drug targets, encouraging the development of inhibitors against various pathway enzymes. 9,13,3841 However, despite resource-intensive efforts that led to the identification of potent inhibitors of Mtb PanC and PanK enzymes, these molecules failed to translate into lead compounds with significant whole-cell activity. 13,42,43 Using cKD mutants of Mtb as tools to assess target vulnerability and the target selectivity of small-molecule inhibitors in whole Mtb cells, we 21 and others 43 concluded that these failures might be explained, at least in part, by the relative invulnerability of Mtb to depletion of PanC and PanK.…”
mentioning
confidence: 99%
“…3537 These studies, together with the availability of crystal structures of a number of CoA pathway enzymes for use in structure-guided drug design, provided further support for investigating the CoA pathway as an attractive source of new TB drug targets, encouraging the development of inhibitors against various pathway enzymes. 9,13,3841 However, despite resource-intensive efforts that led to the identification of potent inhibitors of Mtb PanC and PanK enzymes, these molecules failed to translate into lead compounds with significant whole-cell activity. 13,42,43 Using cKD mutants of Mtb as tools to assess target vulnerability and the target selectivity of small-molecule inhibitors in whole Mtb cells, we 21 and others 43 concluded that these failures might be explained, at least in part, by the relative invulnerability of Mtb to depletion of PanC and PanK.…”
mentioning
confidence: 99%
“…The wild type variant of DPCK performs phosphotransferase activity from ATP to dCoA where dCoA acts as the leading substrate and ATP does not get hydrolysed in its absence (30). The unliganded DPCK is a well folded protein with high α-helical content, its domain movements upon ATP binding play a crucial role during catalysis (28).…”
Section: Discussionmentioning
confidence: 99%
“…The unliganded DPCK is a well folded protein with high α-helical content, its domain movements upon ATP binding play a crucial role during catalysis (28). None of the aromatic amino acid residues has been reported essential for the ligand binding and catalysis (30).…”
Section: Discussionmentioning
confidence: 99%
“…All previously characterized DPCKs are considered to be ATP dependent, although direct experimental evidence is limited. In bacteria, DPCK enzymes from Thermus thermophilus HB8 (31), Mycobacterium tuberculosis (3234), Streptomyces peucetius ATCC 27952 (35), and E. coli K-12 (36) have been characterized.…”
Section: Discussionmentioning
confidence: 99%